Modell Deutschland? Comparative reflections on the German federal system - Fenna, Alan (Springer, 2020)
The chapter reviews the key features that together give German federalism its distinctive character, and reflects on their operation and evolution over the seventy years since Germany’s current constitution, the Grundgesetz, was adopted in 1949. Those distinctive features include: its ‘administrative’ approach to the division of powers; its uniquely ‘federal’ second chamber; the balanced contribution of judicial review; the ‘eternity’ guarantees; the frequency with which formal amendment occurs; the coexistence of federalism and a unitary political culture; the requirement for equality/equivalence of living conditions across the country; and the extent to which it embodies its ancient roots, despite great historical discontinuities. The chapter reflects on some of the similarities and contrasts with federal practices elsewhere and asks to what extent these elements combine to form a coherent and successful federal order.